2021
DOI: 10.1136/jitc-2021-002474
|View full text |Cite
|
Sign up to set email alerts
|

Statin-mediated inhibition of RAS prenylation activates ER stress to enhance the immunogenicity of KRAS mutant cancer

Abstract: BackgroundStatins preferentially promote tumor-specific apoptosis by depleting isoprenoid such as farnesyl pyrophosphate and geranylgeranyl pyrophosphate. However, statins have not yet been approved for clinical cancer treatment due, in part, to poor understanding of molecular determinants on statin sensitivity. Here, we investigated the potential of statins to elicit enhanced immunogenicity of KRAS-mutant (KRASmut) tumors.MethodsThe immunogenicity of treated cancer cells was determined by western blot, flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…In the KRAS-mutant lung cancer model, blockade of both PD-1 and helix-loop-helix transcription factor inhibitor of differentiation 1 knock out significantly enhances the amount of CD8 + T cells as well as the expression of PD-L1, which impairs the tumor growth and increases the survival [126] . In other studies of KRAS mut lung cancer, anti-PD-1 combined with inhibition of the AKT-mTOR pathway by mTOR inhibitor or the STAT3 pathway by natural compound luteolin can remarkably decreased the expression of PD-1 or PD-L1, respectively, which consequently surmounts the resistance to anti-PD-1 [127,128] .…”
Section: Prospective Strategies For Overcoming Resistance To Icismentioning
confidence: 87%
“…In the KRAS-mutant lung cancer model, blockade of both PD-1 and helix-loop-helix transcription factor inhibitor of differentiation 1 knock out significantly enhances the amount of CD8 + T cells as well as the expression of PD-L1, which impairs the tumor growth and increases the survival [126] . In other studies of KRAS mut lung cancer, anti-PD-1 combined with inhibition of the AKT-mTOR pathway by mTOR inhibitor or the STAT3 pathway by natural compound luteolin can remarkably decreased the expression of PD-1 or PD-L1, respectively, which consequently surmounts the resistance to anti-PD-1 [127,128] .…”
Section: Prospective Strategies For Overcoming Resistance To Icismentioning
confidence: 87%
“…RAS signaling in human cancer cells has anti-endoplasmic reticulum stress effect. Inhibition of RAS prenylation enhances endoplasmic reticulum stress and leads to the CD8(+) T cell-mediated cell death of colon cancer cells [ 214 ]. Palmitoylation stabilizes the programmed-death ligand 1 (PD-L1) by blocking its lysosomal degradation.…”
Section: Interplay Between Lipids and Immune System In Cancer Cellsmentioning
confidence: 99%
“…This drug, along with others such as, as it was found that 10 patients who had statin treatment after immunotherapy had a much higher survival rate than those who did not receive statin treatment after immunotherapy. Statins was found to overcome resistance to PD-1 blockade therapies and improve the survival rate of KRAS mut tumor models of syngeneic colorectal cancer, genetically engineered lung and pancreatic tumors, indicating that KRAS mutation could be a molecular target for statins to elicit potent tumor-specific immunity ( 41 ). Statins can reduce inflammation by inhibiting isoprenoid synthesis of the mevalonate pathway ( 42 ).…”
Section: Mutant P53 and Mevalonate Pathwaymentioning
confidence: 99%
“…Statins also block inflammatory responses of endothelial cells and T cells by activating Kruppel-like transcription factors KLF2 and KLF4 ( 42 ). However, statins were also found to promote the differentiation of Forkhead box P3 (Foxp3+) CD4+ regulatory T cells (Tregs) cells while blocking the differentiation of proinflammatory helper T (Th17) cells ( 41 43 ). It is important to mention, though, that this finding is only observational and requires further testing to ensure its significance and validity ( 41 43 ).…”
Section: Mutant P53 and Mevalonate Pathwaymentioning
confidence: 99%